2018
DOI: 10.1021/acs.joc.7b02532
|View full text |Cite
|
Sign up to set email alerts
|

Calix[n]arene-Catalyzed Three-Component Povarov Reaction: Microwave-Assisted Synthesis of Julolidines and Mechanistic Insights

Abstract: A new one-pot cascade reaction-based application of Povarov reactions with a p-sulfonic acid calix[4]arene catalyst for the synthesis of a series of 34 julolidine derivatives with substituents at C8 or C9 in good to excellent yields is reported. These microwave-assisted reactions proceeded efficiently, had short reaction times, were metal-free, were low cost, and used an inexpensive, easily available and nontoxic catalyst. These advantages, along with a simple workup procedure, make this protocol a very effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…In this same work, Abranches et al (2018) also elucidated the mechanism of the Povarov reaction under the reaction conditions used . After Mannich‐type reactions between in situ generated imines and 2,3‐dihydrofuran, the oxonium ions 80 and 81 were formed.…”
Section: Construction Of the Julolidine Skeletonmentioning
confidence: 93%
See 2 more Smart Citations
“…In this same work, Abranches et al (2018) also elucidated the mechanism of the Povarov reaction under the reaction conditions used . After Mannich‐type reactions between in situ generated imines and 2,3‐dihydrofuran, the oxonium ions 80 and 81 were formed.…”
Section: Construction Of the Julolidine Skeletonmentioning
confidence: 93%
“…Despite the large reaction time (48 h), compounds 74a and 74d were obtained good yields (98 and 70 %, respectively). More recently, Abranches and co‐workers (2018) reported a new synthetic strategy for obtaining furojulolidines utilizing just 1 mol‐% CX4SO 3 H as catalyst under microwave irradiation, obtaining furojulolidines 75a – q with good to excellent yields in only 20 minutes of reaction (Scheme ).…”
Section: Construction Of the Julolidine Skeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology exhibited a long reaction time (48 h) and the four furojuloli-dines were obtained in 38-98% yields. Abranches et al 29 also reported the synthesis of furojulolidines 109 and 110 by utilizing just 1 mol% of CX4SO 3 H as a recoverable and reusable organocatalyst under microwave irradiation in 20 minutes, obtaining 34 furojulolidines in yields of 45-96% (Scheme 26, B). In 2019, de Paiva et al 30 synthesized the furojulolidines 109 and 110 by applying silica-supported psulfonic acid calix [4]arene (CX4SO 3 HSi(n)), as a recoverable and reusable heterogeneous catalyst, under solvent-free conditions and microwave irradiation for 10 minutes, obtaining furojulolidines in yields of 58-97% (Scheme 26, C).…”
Section: Short Review Synthesismentioning
confidence: 99%
“…In the Povarov reaction, the imine is produced via acid‐catalyzed reaction between anilines and aldehyde and reacts with a nucleophilic alkene through an aza‐Diels‐Alder or Mannich type reaction (Scheme 2) [10,11]. The Povarov reaction with simple alkenes such as styrene gave low yields of corresponding julolidine derivatives in the presence of TFA as an acid catalyst [12]. Recently, a new one‐pot cascade reaction‐based application of Povarov reaction with a p ‐sulfonic acid calix[4]arene catalyst under microwave irradiation has been reported by S. A. Fernendez and co‐workers for the synthesis of a series of julolidine derivatives [13,14].…”
Section: Introductionmentioning
confidence: 99%